Application of Victorian brown coal for removal of ammonium and organics from wastewater. Issue 8 (18th April 2018) - Nazari, Mohammad Amin; Mohaddes, Farzad; Pramanik, Biplob Kumar; Othman, Maazuza; Muster, Tim; Bhuiyan, Muhammed A.
ABSTRACT: Brown coal is a relatively abundant and low-cost material, which has been used as an effective ion-exchanger to remove ammonium from wastewater. In this study, the influences of pH, ammonium concentration and brown coal dose were investigated for removal of ammonium content from synthetic wastewater. Raw brown coal (RBC) treated with base solution has superior ammonium removal efficiency compared to RBC, which was due to chemical alterations and thus greater attachment of ammonium molecules to base-washed brown coal (BWBC), confirmed by Fourier transform infra-red spectroscopy. Scanning electron microscopy-electron diffraction scattering has identified the augmented sodium content in BWBC, which was subsequently replaced with nitrogen upon wastewater treatment. Crystallographic analysis showed a higher crystallinity formed in BWBC compared to RBC, which was likely due to formation of sodium salt crystals during NaOH treatment. Fitting batch experimental results to adsorption kinetic models suggested that the removal of ammonium was mainly governed by the reaction process rather than the physical diffusion mechanism. Both kinetic and isotherm studies confirmed higher adsorption capacity for BWBC compared to RBC. RBC in column mode was also experimented with to show organics removal from a secondary effluent. A comparatively lower removal of organics was obtained due to inability of charge neutralization as both brown coal and organics are positively charged.